2001
DOI: 10.1209/epl/i2001-00577-6
|View full text |Cite
|
Sign up to set email alerts
|

A new phase in ferroelectric oxides: The phase of charge transfer vibronic excitons

Abstract: It is shown, by means of Hartree-Fock-type calculations using the intermediate neglect of the differential overlap (INDO) method, that polaronic-type charge transfer vibronic excitons (CTVE) in ferroelectric oxides could lead to the formation of a new phase. The ground-state energy of this phase of strongly correlated CTVE lies within an optical gap of pure crystal, and is characterized by a strong tetragonal lattice distortion, as well as ferroelectric and antiferromagnetic ordering. It is shown also that clu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 26 publications
1
42
0
Order By: Relevance
“…This characteristic property is practically observed for all self-activated ABO 3 perovskites titanates [4]. The origin of green luminescence has been explained and discussed in many papers by different mechanisms, including self-trapped excitons [5], recombination of electron and hole polarons, charge transfer vibronic exciton [6], donor-acceptor recombination [7], transitions in MeO 6 complexes [8] and structurally disordered titanates [9][10][11]. However, few investigations on this phenomenon in zirconates have been reported [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…This characteristic property is practically observed for all self-activated ABO 3 perovskites titanates [4]. The origin of green luminescence has been explained and discussed in many papers by different mechanisms, including self-trapped excitons [5], recombination of electron and hole polarons, charge transfer vibronic exciton [6], donor-acceptor recombination [7], transitions in MeO 6 complexes [8] and structurally disordered titanates [9][10][11]. However, few investigations on this phenomenon in zirconates have been reported [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 93%
“…The representation of an ordered BaZrO 3 -o model was built through 1 × 1 × 2 supercell (Fig. 5(a) 6 ], as shown in Fig. 5(b).…”
Section: Bazro 3 Structure and Modelsmentioning
confidence: 99%
“…This increases the vibronic interaction and induces a local lattice instability. This results in a formation of the excited state with a new equilibrium charge transfer and lattice relaxation [31,32]. As a result of modelling, we found that the CTVE consists of a pair of spatially well correlated electron and hole polarons localised mainly on the nearest Nb 1 and O 1 atoms.…”
Section: Quantum Chemical Modelling Of Electron Polaronsmentioning
confidence: 79%
“…The origin of this luminescence has been discussed more than once. Suggested mechanisms include donoracceptor recombination [29], recombination of electron and hole polarons, charge-transfer vibronic excitons (CTVE) [30][31][32] and transitions in MeO 6 complexes [33]. In this paper, we perform a modelling of electron polarons and triplet excitons in ABO 3 perovskites and compare calculated optical energies with relevant experiments.…”
mentioning
confidence: 99%
“…Such flat bands could make possible hole and exciton self-trapping. An exciton self-trapping in SrTiOa bulk was indeed discussed quite recently [27].…”
Section: Band Structurementioning
confidence: 82%